2021
DOI: 10.1017/s1463423621000505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diabetes self-management education program on lowering blood glucose level, stress, and quality of life among females with type 2 diabetes mellitus in Thailand

Abstract: Aim: The aim of this study is to assess the effect of diabetes self-management education (DSME) on lowering blood glucose level, stress, and quality of life (QoL) among female patients with type 2 diabetes mellitus (T2DM) in Thailand. Background: The burden of noncommunicable diseases has increased globally, and it has negatively affected the QoL of diabetic patients. Methods: A quasi-experimental study was conducted by including 77 T2DM patients selected from 2 public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
4
8
0
Order By: Relevance
“…But, in our study, individuals who had more education had greater diabetes knowledge. Patients with higher education levels tended to have more knowledge to manage their disease, more confidence in self-management of disease, and were more likely to engage in self-management behaviors such as regular exercise, watching their diet and foot care, and adherence to medication leads to better HbA1c control [17,19]. This support by Persell and collected showed that knowledge patients were more likely to perform self-management activities, patients with T2DM would be more likely to follow a diabetes diet, to self-monitoring their blood glucose level and have regular exercise when their diabetes knowledge was improved [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, in our study, individuals who had more education had greater diabetes knowledge. Patients with higher education levels tended to have more knowledge to manage their disease, more confidence in self-management of disease, and were more likely to engage in self-management behaviors such as regular exercise, watching their diet and foot care, and adherence to medication leads to better HbA1c control [17,19]. This support by Persell and collected showed that knowledge patients were more likely to perform self-management activities, patients with T2DM would be more likely to follow a diabetes diet, to self-monitoring their blood glucose level and have regular exercise when their diabetes knowledge was improved [30].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the cost of diabetes care is sharply rising in Thailand. The annual treatment of diabetes accounted for 23% of all medical costs, with the cost for treating diabetes patients reaching 4.2 times that for non-diabetes patients [17]. These statistics indicate a high mortality rate for diabetes, and economic burden for health care systems.…”
Section: Introductionmentioning
confidence: 99%
“…This research was funded by Poltekkes Kemenkes Bengkulu, Indonesia. be used as an intervention for patient with type 2 diabetes (Nooseisai et al, 2021). Management of selfeducation in patients with diabetes can improve clinical outcomes indicated by the result that after four months of health education, the average HbA1C level is reduced by 12% and the average blood sugar is reduced by 12% (Lavelle et al, 2016).…”
Section: Acknowledgementmentioning
confidence: 99%
“…Stress in diabetic patients also can decrease adherence (29). A previous study found that stress management in people with DM can also reduce the level of glucose (30,31). So, it's important to maintain stress management during COVID-19, especially for people with DM during a pandemic.…”
Section: Avoid Meeting Doctors or Nurses Directly Because They Can Tr...mentioning
confidence: 99%